Analytical and microbiological characterization of 20th century photographic negatives - Coelho, Cátia (2015)
Two cellulose acetate photographic negatives were studied. Photography under transmitted, raking and UV illuminations in conjunction with optical microscopy, VP-SEM-EDS, ATR-FT-IR, Py-GC-MS and EDXRF were used for analytical characterization. Microbiological studies revealed the presence of three bacteria strains colonizing the negatives. Samples present a degraded status, exhibiting channels and bubbles. Triphenyl phosphate was the plasticizer used in the manufacturing process of both negatives. Cross section of one of the samples allowed to distinguish the different layers that compose the negative. Contaminants related to the manufacturing process were discussed.